Pengaruh Tanaman Sirih Gading (Epipremnum aureum) Terhadap Polutan Udara Dalam Ruangan - Yuniar Putrianingsih; Yusriani Sapta Dewi (FT-USNI, 2019)
Air has an important meaning in the life of living things and the existence of other things, so it must be protected for human life and other living things. The utilization must be done by maintaining air quality from air pollution. Indoor air quality is also a problem that needs to get attention because indoor air pollution was larger than the outdoors, which affects human health. As for how to reduce indoor air pollution by utilizing plants, other than as an ornamental plant, some plants can also function as pollutant cleaners. One of them is like the plant used in this research that is Sirih Gading (Epipremnum Aureum). The purpose of this study is to determine the ability of Sirih Gading plants (Epipremnum Aureum) in absorbing indoor air pollutants. The method used are SNI 7119.10: 2011, SNI 16-7058-2004 and NIOSH 1501: 2003. The results obtained are the Sirih Gading plants (Epipremnum Aureum) capable of absorbing carbon monoxide and benzene pollutants but not so much affect the dust particles